WISP1 Predicts Clinical Prognosis and Is Associated With Tumor Purity, Immunocyte Infiltration, and Macrophage M2 Polarization in Pan-Cancer - Liao, Xia; Bu, Yang; Xu, Zihan; Jia, Fengan; Chang, Fan; Liang, Junrong; Jia, Qingan; Lv, Yi (Frontiers in Genetics, 2020)
Cancer is becoming the leading cause of death and a major public health problem. Although many advanced treatment strategies are currently in use, including molecular targeted therapy and immunotherapy, the general prognosis of cancer patients remains dismal due to the high frequency of recurrence, metastasis, and drug resistance. In this study, we comprehensively analysed WNT1-inducible-signaling pathway protein 1 (WISP1) expression and explored its correlation with prognosis in pan-cancer using Tumor IMmune Estimation Resource (TIMER) and Gene Expression Profiling Interactive Analysis 2 (GEPIA2). We also examined correlations between WISP1 expression and immunocyte infiltration using TIMER. We identified genes co-expressed with WISP1 using the LinkedOmics database and analysed associated gene ontology using Metascape. Finally, we constructed protein-protein interaction networks and examined correlations between genes co-expressed with WISP1 and immunocyte infiltration in pan-cancer. WISP1 mRNA levels differed between human pan-cancer tissues and normal tissues, indicating its potential as a prognostic biomarker. WISP1 expression was correlated with tumour purity and immunocyte infiltration, especially monocyte-macrophage trafficking and M2 polarization. Genes co-expressed with WISP1 were mainly associated with extracellular matrix organization, with the collagen members COL6A3, COL5A1, and COL8A1 being key coincident genes correlated with macrophage infiltration and M2 polarization in pan-cancer. Conversely, in certain type of cancer with better prognosis, WISP1 expression associated with low immunocyte infiltration and M2 macrophage polarization. These results suggest that WISP1 may modulate clinical prognosis through its associations with tumour purity, immune cell infiltration, and macrophage M2 polarization in pan-cancer, with collagen members proteins serving as effector molecules of WISP1.